Knock-in Mouse Model for Resistance to Thyroid Hormone (RTH): An RTH Mutation in the Thyroid Hormone Receptor Beta Gene Disrupts Cochlear Morphogenesis - Griffith, Andrew J. (Springer-Verlag, 2002)
Thyroid hormone and the beta isoform of its receptor, Trb, are essential for normal development of the mammalian auditory system. We have analyzed auditory system function and structure in a mouse strain with a targeted Thrb mutation, ThrbPV, which leads to the loss of binding of thyroid hormone (T3) to the Trb protein. Heterozygosity for the orthologous human THRBPV mutation and other similar mutations in human THRB cause resistance to thyroid hormone (RTH), which is occasionally associated with mild sensorineural hearing impairment. Auditory brainstem response analysis of heterozygous ThrbPV/+ mice demonstrates that they develop normal hearing. In contrast, ThrbPV/ThrbPV mice have severe hearing impairment that is already present at 3 weeks of age. This hearing loss is associated with disruption of postnatal morphogenesis of the tectorial membrane and organ of Corti. Comparison with the previously described phenotype of a Thrb ?/? knockout strain suggests that ThrbPV disrupts the function of other genes that are critical for development and/or maintenance of these structures.